Same words, different meanings: examining curriculum making from the perspective of language teachers’ epistemic beliefs - Kheir-Farraj, Roseanne; Orland-Barak, Lily (Frontiers in Education, 2025)
IntroductionGiven the predominant psycholinguistic approach to language education, little is known about the epistemic beliefs of language teachers and how they shape the enactment of reformed language curricula. These beliefs are mostly researched in science education but less in language education. To fill this gap, we investigated the epistemic beliefs of Arabic-speaking teachers of English in Israel and how they converge with or diverge from the epistemic underpinnings of the national English curriculum.MethodsWe collected data from 44 teachers primarily via personal and group interviews in 11 school settings. We also observed staff meetings and collected artifacts from teachers. We asked how teachers understand the notion of academic literacy, and how their understanding of literacy (mis)aligns with the epistemic orientation of the English curriculum in Israel. We used interpretative phenomenological analysis to uncover teachers’ implicit epistemic beliefs by probing into their interpretations of the curriculum’s teaching goals and learning principles.ResultsThematic analysis revealed three major misalignments relating to the function of literacy in the lives of language learners, the features of literacy, and the fields of responsibility of teachers and learners. These misalignments were found even though teachers drew on the same terminology of the reformed curriculum when talking about their practice.ConclusionFindings indicate that teachers employ a different sense of literacy than intended in the curriculum. Theoretically, insights about teachers’ epistemic beliefs, which are mostly implicit, helped us explain the explicit pedagogical and instructional beliefs that are widely held by language teachers across language teaching contexts. Practically, the study suggests that policymakers, curriculum designers, and teacher educators need to be aware of the implicit epistemic beliefs of language teachers and the way these beliefs can shape how teachers enact language reforms.